Analysis Of The Gap Between The Process Of Forming Legislation And The Decision Process Of The Constitutional Court - Suhaeri Suhaeri (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This article explains the gap between what was decided in the legislative process and the decision given by the Constitutional Court. This type of research is qualitative research with a normative juridical approach. As well as descriptive analysis methods. The results of this research show that the gap between the legislative process and the decision of the Constitutional Court occurs at the stage of discussing the bill and its academic text which is carried out only by the DPR and the President and DPD, while in the Constitutional Court the most decisive stage is at the trial examination stage and the Judges Deliberation Meeting ( RPH) which is the stage of deciding a case carried out by selected and selected judges who certainly have a better quality of understanding in understanding the 1945 Republic of Indonesia Constitution. It is important to maintain harmonization between the legislative process and the decisions of the Constitutional Court to maintain justice and order in society, then the proposal of this article is that the national legislative body should establish a Court like the Constitutional Court which consists of judges who are selected in the same manner as judges are elected in the Constitutional Court. These judges will later be tasked with providing plenary decisions on a legislative process.